HUBUNGAN ANTARA DUKUNGAN TEMAN SEBAYA DENGAN KONSEP DIRI PADA REMAJA PUTUS SEKOLAH - Siti Anggraini; Jumaini Jumaini; Febriana Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The rates of adolescent dropout from school is still high enough until now. This phenomenon will affect adolescent selfdevelopment include the development of self-concept. Peer has a big influence on the development of adolescent selfconcept especially adolescent who live in the social institution. This study aims to determine the correlation between peer support with self-concept in the adolescent drop out of school with descriptive design correlation and cross sectional approach. The sample of this research is 70 respondents. The samples are taken by a total sampling technique. This measurement tool have been tested valid and reliable. The result of valid and reliable test to peer support questionnaire that is (r of count is 0,466-0,865) dan (alpha value > r table is 0,933 > 0,444) and result of valid and reliable test to self-concept questionnaire that is (r of count is 0,322-0,737) dan (alpha value > r table is 0,937 > 0,312). The analysis used is univariate analysis used descriptive test to know frequency distribution of respondent characteristics and bivariate analysis of used is a chi-square test to know correlation between peer support and selfconcept in the adolescent drop out from school. The result showed that there is a significant correlation between peer support and self-concept in the adolescent drop out from school with (p-value 0,002< 0,05: OR = 4,752). Adolescent dropout from school should develop mutually supportive relationships with peer group so that to always the formation of positive self-concept.  Keywords: Adolescent dropout of school, peer support, self-concept.